Improving Students Writing Skill with Collaborative Writing Learning Strategy through Edmodo - Candra Hadi Asmara; Merinda Fiana Tasri (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2020)
Through the development and advancement of technology in writing classes, Collaborative Writing can be done by using the World Wide Web to maximize the process. Collaborative Writing itself involves more than one person to contribute to making the text so of course in the learning process sharing roles and responsibilities is very necessary. However, the use of Collaborative Writing is not enough because in fact, based on previous research there are still some deficiencies found in Collaborative Writing, so combining it with an appropriate and interesting media is needed. The researcher chooses Edmodo as their learning media, Edmodo can be used for collaborative writing where all students can contribute to making good writing. By using Edmodo in Collaborative Writing students can interact and write together with other students to developing their writing. The purpose of this study is to combine the Collaborative Writing strategy through Edmodo to improve students' writing skills. The research model used was Classroom Action Research with 10th-grade students s the subject. Furthermore, data collection techniques used are Observation, Interview & Test. The findings of this study prove that the use of Collaborative Writing through Edmodo is very effective in improving students' writing skill. Improvements can also be shown based on findings from observations that show positive reactions and excellent responses from students. The researcher also briefly recommends the use of this strategy and media to be applied in other ways, skills and at different levels.